2011
DOI: 10.1063/1.3637946
|View full text |Cite
|
Sign up to set email alerts
|

Chiral hide-and-seek: Retention of enantiomorphism in laser-induced nucleation of molten sodium chlorate

Abstract: We report the observation of non-photochemical laser-induced nucleation (NPLIN) of sodium chlorate from its melt using nanosecond pulses of light at 1064 nm. The fraction of samples that nucleate is shown to depend linearly on the peak power density of the laser pulses. Remarkably, we observe that most samples are nucleated by the laser back into the enantiomorph (dextrorotatory or levorotatory) of the solid prior to melting. We do not observe a significant dependence on polarization of the light, and we put f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…[1][2] Non-photochemical LIN (NPLIN) generally requires relatively lower intensities of light at wavelengths where there are no strong absorption bands in the system; short, unfocussed pulses (ps to ns) of laser light are typically used. Systems that have been studied using NPLIN include small molecules such as glycine and carbamazepine, [3][4][5][6][7][8][9] simple salts such as KCl, [10][11][12] singlecomponent systems such as acetic acid and sodium chlorate, [13][14] and large molecules such as proteins. [15][16] The main advantage of NPLIN is that it appears to be similar to homogeneous 2 nucleation: it requires only solute and solvent, occurs in the bulk of the solution, and there is no chemical damage to molecules.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2] Non-photochemical LIN (NPLIN) generally requires relatively lower intensities of light at wavelengths where there are no strong absorption bands in the system; short, unfocussed pulses (ps to ns) of laser light are typically used. Systems that have been studied using NPLIN include small molecules such as glycine and carbamazepine, [3][4][5][6][7][8][9] simple salts such as KCl, [10][11][12] singlecomponent systems such as acetic acid and sodium chlorate, [13][14] and large molecules such as proteins. [15][16] The main advantage of NPLIN is that it appears to be similar to homogeneous 2 nucleation: it requires only solute and solvent, occurs in the bulk of the solution, and there is no chemical damage to molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For nucleation of simple salts from solution, the interaction of the transient E-field with a sub-critical cluster acts to lower its free energy, causing a change in its structure. 10,12 In the case of small molecules, the difference in polarizability along different directions of the molecule means that molecules can become aligned with respect to the direction of the E-field, analogous to the optical Kerr effect (OKE). 5,19 The resulting increase in structural order due to the interaction between the E-field and solute cluster gives rise to nucleation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Theoretical simulations by Knott et al, however, suggest that the free energy gain from the orientational bias at the electric field strengths involved are not sufficient to explain NPLIN by the OKE mechanism. 30 Alexander and co-workers have studied NPLIN of a number of metastable systems, 31,32 in particular the benchmark system of aqueous potassium chloride (KCl). 24,33,34 It was demonstrated that samples of KCl with supersaturations (S = C/C sat ) in the range 1.05-1.10 can be nucleated by a single pulse from a nanosecond laser.…”
Section: Introductionmentioning
confidence: 99%